Microstructure Evolution and Mechanical Properties of a Powder Metallurgy Ti‐22Al‐25Nb Alloy Processed through Isothermal Rolling and Solution and Aging Treatment. Issue 2 (22nd October 2019) - Jia, Jianbo; Lu, Chao; Zhong, Xiaoxiao; Yang, Zhigang; Xu, Yan; Sun, Wei; Luo, Junting
Abstract : Isothermal rolling is conducted at 1050 °C (α2 + B2 phase region) and 1100 °C (B2 phase region) for a spark plasma sintering (SPS)‐processed Ti‐22Al‐25Nb alloy. The effects of rolling temperature, pass, reduction per pass, and solution and aging on microstructure evolution, phase transformation, and tensile property at ambient temperature are systematically investigated. The results show that as the alloy is rolled at 1050 °C for 1 pass (P), the optimal tensile strength (TS) and the yield strength (YS) are 964.78 and 935.16 MPa, respectively, and the elongation ( δ ) reaches 23.65%. Then, followed by a subsequent solution and aging at 940 °C/30 min/water quenching (WQ) + 760 °C/24 h/air cooling (AC), it exhibits a decrease in mechanical properties. Moreover, a mixed fracture mechanism dominated by ductile fracture is shown for the as‐rolled alloy. However, after a solution and aging, it is transformed to a mixed fracture mechanism dominated by brittle fracture, which attributes to the void aggregation and the development of the discontinuous brittle α2 precipitates along B2 matrix grains during the solution and aging treatment. Finally, fracture models of the as‐rolled alloy and the solution and aging‐treated alloy are established. Abstract : The effects of rolling parameters and heat‐treatment on microstructure evolution and mechanical property of the powder metallurgy Ti‐22Al‐25Nb alloy are investigated. The fracture models are established. The alloy rolled at 1050 °C/1 Pass exhibits the better tensile strength, yield strength, and elongation, which are increased to 102.51%, 102.62%, and 230.06% of initial alloy.